Analisis Kesalahan Siswa SMK dalam Menyelesaikan Soal Aljabar Berbasis Teori Kastolan - Raya Djatnika Sudjanta; Muhammad Adam Fahri A.; Raisyal Fiqri Perdana Sasmita; Rejepguly Abdullayev (JURNAL RISET RUMPUN MATEMATIKA DAN ILMU PENGETAHUAN ALAM, 2024)
The concept of algebra is very important in learning mathematics, students' ability to understand advanced mathematics lessons depends on mastery of algebraic concepts. Therefore, it is necessary to analyze the errors that often arise when students solve algebra problems. The purpose of this study is to analyze the errors of vocational students in class XI in solving algebra problems. This research uses a qualitative method that is analyzed descriptively. The research subjects were 28 students of class XI with the object of research, which is the errors that arise when students solve algebra problems. The results showed that based on Kastolan's Theory, procedural errors occur most often, followed by technical errors, and concepts.